Gross Violations of Human Rights Veiled within Xinjiang Political Reeducation Camps - Rakhima, Ayu Suci; Satyawati, Ni Gusti Ayu Dyah (Kertha Patrika; Vol 41 No 1 (2019), 2019)
Xinjiang reeducation camps are dedicated to cleanse the practice and existence of religion, and majorly subjects the Uighur moslems. China has constantly denied the conduct of gross human rights violations of Uighur moslems within Xinjiang political reeducation camps. This article will elaborate on the actions done by Xinjiang officials to unveil the gross violations of human rights towards the Uighurs within Xinjiang reeducation camps. The article will also examine the available possibility to criminally hold the perpetrators liable and provide effective relief to the victims. This article is constructed using normative legal research method with statutory, case, and fact approaches, along with conceptual/analytical approach. The result shows that there exist gross violations of human rights towards the Uighurs within Xinjiang reeducation camps in a form of arbitrary detention and torture. Moreover, there are some available possibilities to criminally hold the perpetrators liable and provide effective relief to the victims, namely through a municipal court proceeding and through the Committee against Torture.